Respon Beberapa Varietas Tanaman Kacang Panjang (Vigna sinensis L) Pada Pemberian Dosis Pupuk Kandang Kelinci - Anak Agung Yuni Astari; Anak Agung Ngurah Mayun Wirajaya; Luh Kartini (Fakultas Pertanian, Universitas Warmadewa, 2019)
This study aims to determine the response of several varieties of long bean plants (Vigna sinensis L.) to the administration of rabbit manure doses. This research was conducted in Subak Pagutan, West Denpasar District, Denpasar City. The height of the place is at 75 m above sea level and the average temperature of 27-32 0C was carried out on April 8 to June 25, 2018. The design used in this study was a Randomized Block Design (RBD) consisting of 2 factors, namely: The dosage treatment of Rabbit Manure consists of 3 levels, namely: D0 (0 tons ha-1), D1 (5 ton/ha), D2 (10 ton/ha), and D3 (15 tons/ha). Variety treatment consists of 3 levels, namely: V1 (Pertiwi Varieties), V2 (Tavi Parade Varieties), and V3 (Patria BM Varieties). In the treatment of rabbit manure dose of 5 tons / ha (D1) gave the highest yield on the fresh weight of pods per plant that is 693.35 g, an increase of 28.71% when compared with the lowest fresh weight of harvested pods, namely the treatment of rabbit manure dose of 15 tons/ha (D3) which is 538.66 g. The highest fresh weight of pods per plant obtained in the treatment of Pertiwi (V1) 708.21 g was not significantly different from the treatment of Pertiwi (V2) 636.95 g and significantly different from the treatment of Patria BM (V3) 494.21 g. An increase of 43.30%, 29.48% when compared with the lowest in the treatment of Patria BM (V3) varieties, namely 494.21 g